2022
DOI: 10.4103/njm.njm_65_22
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological Endoscopic Procedures in a Tertiary Hospital in South-West Nigeria

Abstract: Background: After several years of struggling due to many constraints, centers in Nigeria are now performing Gynecological Endoscopy (GE) procedures. This study describes the outcome of various GE procedures in patients with gynecological complaints in a tertiary hospital in South-West Nigeria. Materials and Methods: This study was a prospective longitudinal design. All eligible patients who had endoscopic procedures in the unit between May 2014 and Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Room air can also be used safely with minimal complications, especially in low-resource settings like ours (22)(23)(24). Although cheaper and readily available, room air is associated with poorer visibility, increased risk of wound infection, and abdominal discomfort compared with Carbon dioxide (25)(26)(27). Other gases that can be used are Nitrous oxide, Helium, and Xenon (21).…”
Section: It Is Usually Associated With Immense Psychosocial Challenge...mentioning
confidence: 99%
“…Room air can also be used safely with minimal complications, especially in low-resource settings like ours (22)(23)(24). Although cheaper and readily available, room air is associated with poorer visibility, increased risk of wound infection, and abdominal discomfort compared with Carbon dioxide (25)(26)(27). Other gases that can be used are Nitrous oxide, Helium, and Xenon (21).…”
Section: It Is Usually Associated With Immense Psychosocial Challenge...mentioning
confidence: 99%
“…A study by Onoh et al 16 in Southeast Nigeria showed that the major challenges bedeviling endoscopy were: late report of endoscopic-related cases, inadequate equipment, lack of maintenance, unstable power supply and wrong notion by the population. However, Fehintola et al 20 in a study in Southwest Nigeria, reported zero mortality in 287 patients that underwent various degree of endoscopic interventions and thus documented local adaptation and improvised approach as the ways to make endoscopy affordable and easily accessible.…”
Section: Introductionmentioning
confidence: 99%